Write an expression that is equivalent to (4x+3)+(-2x+4)

Answers

Answer 1
Answer: Combine like terms

2x+7

Related Questions

Simplify each expression below as much as possible. 6x + 2 - 1 - 4x - 3 - 2x + 2
How many feet are in 42 inches
2 mi. yd. I'm confused​
If there are 5 fish and 1 of the dies how many are left ​
jermey has a weekend job as soccer referee. one weekend, he earns $140 by working 4 games. another weekend he earns $210 by working 6 games. if jeremy graphed an equation that represented his total earning based on the number of games worked, what would be the slope of the graph

The expression 63 × 42 is equivalent to which of the following numerical expressions? 18 x 8


B.

(6 x 4) 5


C.

246


D.

216 x 16

please answer

Answers

The required equivalent expression is (216 x 16).

The correct is D.

What is Expression?

In mathematics, an expression is a phrase that has at least two numbers or variables and at least one maths operation. Addition, subtraction, multiplication, or division are all examples of maths operations. An expression's structure is as follows:

(Number/variable, Math Operator, Number/variable) is an expression.

We have the Expression as,

6³ x 4²

Now, expand the exponents as

= 6 x 6 x 6

= 216

and, 4² = 4 x 4 = 16

Thus, the required equivalent expression is (216 x 16).

Learn more about expression here:

brainly.com/question/14083225

#SPJ2

Answer:

2646

Step-by-step explanation:

is the correct answer for This question

{x}^(2)  +  √(x)  +  \sqrt[5]{x}
what is f'(3) of this equation?​

Answers

Answer:

3 + (1)/(2√(3) ) + \frac{1}{5\sqrt[5]{81} }

Step-by-step explanation:

Just to make it easier to see, √(x) = x^{(1)/(2) } and \sqrt[5]{x} = x^{(1)/(5) }  This way we could more easily use the power rule of derivatives.

So if f(x) = x^(2) +x^{(1)/(2) } +x^{(1)/(5) } then f'(x) will be as follows.

f'(x) = x^(1) +(1)/(2) x^{-(1)/(2) } +(1)/(5) x^{-(4)/(5) } = x +\frac{1}{2x^{(1)/(2) }} +\frac{1}{ 5x^{(4)/(5) }} = x +(1)/(2√(x)) +\frac{1}{ 5\sqrt[5]{x^4} }

to find f'(3) just plug 3 into f'(x) so 3 + (1)/(2√(3) ) + \frac{1}{5\sqrt[5]{81} }

How do I solve this?

Answers

Answer:

Step-by-step explanation:

Just so that we have something to work with, the length of the longest day (June 22) in Acron Ohio is 15 hours 8 minutes and 9 seconds on the 20th of June of this year. The number we get won't be this accurate, but it will tell us if we have done it correctly. The tricky part is when to use the radians.

cos(0.1309 H) = -0.4336 tan (40o 46 minutes)  I have assumed this is in radians. It won't work any other way. The measurement cannot be in degrees which will give a negative tan from the minus sign out in front. The cos being minus will make things even worse.

cos(0.1309 H) = -0.4336 tan (40 46/60  )

cos(0.1309 H) = -0.4336 tan (40.766666667)

cos(0.1309 H) = -0.4336 * -0.074173405

cos(0.1309 H) = 0.032161588

0.1309 H = cos-1(0.032161588)

0.1309 H =  1.538629191

H = 1.538629191 / 0.1309

H = 11.754 which is no where near 15 hours, but it is what the numbers give.

I would suggest that you go to your instructor for the other two. Work this one out until you get somewhere near 11.7 hours.

The other two cities should come to something near  this answer.  

Answer:

Step-by-step explanation:

Slope= -3/1

plot from point  (-2,4)

A bag contains 10 w h i t e marbles, 5 g r e e n marbles, 6 y e l l o w marbles. If two different marbles are drawn from the bag , what is the probability of drawing a w h i t e marble then a y e l l o w marble?

Answers

Answer:

1/7

Step-by-step explanation:

If a bag contains 10 white marbles, 5 green marbles, 6 yellow marbles and two marbles are drawn at random, the probability of picking a white marble and then a yellow marble means a white marble was picked first and then followed by yellow marble.

Note that the white marble that was picked first was not replaced. This is a probability question without replacement.

Probability of an event = possible outcome of event/Total outcome of event

Total outcome = total number of marbles = 10+5+6 = 21marbles

If a white marble is selected first, the probability of selecting a white marble will be 10/21.

Since the white ball wasn't replaced, the new total number of marbles will become 21-1 = 20marbles

If yellow marble was then selected out of this 20 marbles remaining, the probability of selecting the yellow marble will be 6/20 {since there are 6yellow marbles}

The probability of drawing a white marble and then a yellow marble will then give us;

10/21×6/20

= 60/420

= 6/42

= 1/7(in its simplified form)

Question 3 (1 point) If the following is a rhombus, find the missing measures. Find PQ. PQ=​

Answers

Answer:

Step-by-step explanation:

PQ*PQ=PQ²=(5x+16)²=25x²+160x+256

Please, I need help! a positive integer is subtracted from its square. The sum is 56. Write and solve a quadratic equation to find the number. Thank you!

Answers

Answer:

8

Step-by-step explanation:

x² − x = 56

x² − x − 56 = 0

(x − 8) (x + 7) = 0

x = -7 or 8

x is positive, so x = 8.